2013
DOI: 10.29074/ascls.26.2.89
|View full text |Cite
|
Sign up to set email alerts
|

Do Elevated Hematocrits Prolong the PT/aPTT?

Abstract: The Clinical and Laboratory Standards Institute guidelines require special processing of whole blood specimens with hematocrits greater than 55% due to the possibility of spurious prolongation of routine coagulation studies (PT, aPTT). As samples with hematocrits above 60% are rare at our institution, our study seeks to determine the effect of relative citrate excess on routine coagulation studies in samples with hematocrits of 60% to determine whether special processing is necessary. A calculated volume of 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…As a result, high hematocrit levels are likely to be encountered by clinical laboratories with relative frequency [7]. However, data suggest that routine coagulation tests can be conducted and analyzed with certainty using samples with hematocrits of up to 60% [8]. Similarly, for hematocrit values below 25% (<0.25), there is no requirement to modify the citrate concentration [9].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, high hematocrit levels are likely to be encountered by clinical laboratories with relative frequency [7]. However, data suggest that routine coagulation tests can be conducted and analyzed with certainty using samples with hematocrits of up to 60% [8]. Similarly, for hematocrit values below 25% (<0.25), there is no requirement to modify the citrate concentration [9].…”
Section: Discussionmentioning
confidence: 99%
“…There are several articles in the literature with this recommendation, but most of them are reviews [ 1 , [6] , [7] , [8] , [9] ], with few research-based articles [ 3 , 16 ]. There is a specific recommendation for using citrate-adjusted tubes from CLSI that can be found in NCCLS document H21-A5 [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Austin M et al. [ 16 ] used thromboplastin extracted from rabbit brain to perform PT tests on samples with artificially high Ht, in which a sufficient volume of 3.2% buffered sodium citrate was added to aliquots to simulate a hematocrit of 60% (final citrate/plasma ratio of 1:3.6). The results of this analysis suggested that the PT test from samples with Ht up to 60% may be performed and interpreted with confidence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to sampling from the wrong patient or using inappropriate anticoagulant tubes for sample collection, incorrect sample volume, clotted samples, hemolysis, and lipemia, the patient's age, gender, ethnic group, blood group, physical activity level, stress status, circadian and diurnal rhythm and anticoagulant use are also suggested as preanalytical causes affecting coagulation tests [5,6]. Moreover, the hematocrit values of the patient are another pre-analytical factor that might influence test results [5,7].…”
Section: Introductionmentioning
confidence: 99%